Habits of mind and Emotional Tranquility for Preparatory stage students (Journal of the College of Basic Education, 2022)
the research objectives are conducted to the following :1- To know the level of Habits of the mind with the high school students. 2- To know the level of Emotional Tranquility with high school students. 3-To know the relationship between Habits of the mind and Emotional Tranquility with high school students.The current research contained a sample of high school students mostly from the fifth stage (scientifical and literary) for both males and females in the city of Baghdad (morning studies) for 2016-2017. Theoretical frame :This research viewed several adopted theories in constructing and explaining results. The research measures : 1-The researcher has Adopted the Habits of the mind scale which was prepared by a group of professional researchers at the university of Vermont (Costa and Kallick) and she also adopted the Emotional Tranquility scale (Atwan2015) after assuring its credibility and stability and the manner of answering each paragraph. 2-The two mentioned measures were applied on a sample averaging between (200) students for both males and females students during 20 - 29/12/2016, the researcher has used the following Data for analyzing results with the help of the statistic programs for social sciences in data process(SPSS)As a result, it had been reached the results that are listed below 1- The research results showed that high school students adopted Habits of the mind. 2- the results revealed that the sample has the Emotional Tranquility 3-the Results showed that there is a positive connection or relationship between Habits of mind and Emotional Tranquility in the studentsThe researcher has submitted some recommendations and suggestions